Faking by actual applicants on personality tests: A meta‐analysis of within‐subjects studies - Hu, Jing; Connelly, Brian S. (International journal of selection and assessment, 2021)
Background Researchers have used within‐subjects designs to assess personality faking in real‐world contexts. However, no research is available to (a) characterize the typical finding from these studies and (b) examine variability across study results. Aims The current study was aimed at filling these gaps by meta‐analyzing actual applicants’ responses to personality measurements in high‐stakes contexts versus low‐stakes contexts reported in within‐subjects studies. Materials & Methods This meta‐analysis examined 20 within‐subjects applicant–honest studies (where individuals completed an assessment once as applicants and again in a low‐stakes setting). Results We found that applicants had moderately higher (more socially desirable) means, slightly reduced variability, and stronger rank‐order consistency in high‐stakes settings. The assessment order moderated the findings; studies with a high‐to‐low order (where the high‐stakes setting was introduced first) showed a stronger faking effect—demonstrated by higher means and weaker rank‐order consistencies—than those in a low‐to‐high order. Discussion and Conclusion These findings are consistent with expectations that, relative to low‐stakes situations, individuals tend to exaggerate, in a positive direction, their personality descriptions as job applicants. In addition, assessment order matters when understanding the magnitudes of faking effects.